Forest loss and Borneo's climate. (23rd March 2018) - McAlpine, Clive A; Johnson, Alex; Salazar, Alvaro; Syktus, Jozef; Wilson, Kerrie; Meijaard, Erik; Seabrook, Leonie; Dargusch, Paul; Nordin, Haziq; Sheil, Douglas
Abstract: The equatorial island of Borneo is a deforestation hotspot. However, the influence of forest loss on the island's climate remains largely unexplored. Here, we examine how forest loss is related to changes in ground-based records of temperature (1961–2007) and precipitation (1951–2007), and MODIS data for temperature (2002–2016). Analyses were performed for the entire island, lowland areas (<200 m ASL), and nine selected watersheds. We found a strong island-wide relationship between forest loss and increases in daily temperature and reductions in daily precipitation. The relationship between deforestation and changes in local climate was most pronounced for watersheds in southeast Borneo, which have lost 40%–75% of their forests since 1973. These watersheds also had a significantly higher frequency of temperatures above 31 °C. Watersheds in north and northwest Borneo, which have lost 5%–25% of their forest cover, maintained a more stable climate with a similar distribution of mean and extreme warm temperatures between forest and modified forest areas. Watersheds with >15% forest loss had a >15% reduction in rainfall. We conclude that loss of forest in Borneo has increased local daily temperatures and temperature extremes, and reduced daily precipitation.